Susceptibility of Diaphorina citri to dimethoate and chlorpyrifos in commercial citrus orchards of Veracruz, Mexico - Zamora Juárez, Sherell; Rodríguez-Lagunes, Daniel Arturo; Osorio-Acosta, Francisco; Castañeda-Castro, Odón; Núñez-Pastrana, Rosalía; Noa-Carrazana, Juan Carlos (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
There are reports of Diaphorina citri resistance in the state of Veracruz to chlorpyrifos and dimethoate due to the excessive use of these products for the control of pests, among them D. citri. The purpose of this work was to diagnose the susceptibility of D. citri adults to chlorpyrifos and dimethoate in commercial citrus orchards of the municipality of Martinez de la Torre, Veracruz. For this, 200 adults of D. citri were collected in each of 30 orchards, and topical application bioassays were performed with dimethoate at 0.0090% concentration and chlorpyrifos at 0.0085% concentration. Diaphorina citri adults without chemical control during 10 years were used as a control. Mortality of D. citri with dimethoate and chlorpyrifos averaged 85%, in contrast the control mortality was 99% and 98.8% with dimethoate and chlorpyrifos, respectively. According to these results, it can be inferred that D. citri has some resistance to organophosphate insecticides in the orchards of Martinez de la Torre, Veracruz. This information can be used to decide the type of insecticides to apply in the study area.